Comparing the Ecological Niches of Chlamydial and Gonococcal Infections in Winnipeg, Canada: 2007–2016. Issue 11 (November 2021) - Shaw, Souradet Y.; Elliott, Lawrence J.; Nowicki, Deborah L.; Green, Christopher G.; Ross, Craig P.; Reimer, Joss N.; Wylie, John L.; Plourde, Pierre J.; Aral, Sevgi O.; Becker, Marissa L.; Blanchard, James F.
Abstract : This population-based study from Winnipeg, Canada demonstrated that although chlamydia and gonorrhea infections impacted different demographic groups, gonorrhea infections during a growth phase occupied similar geographic spaces as chlamydia infections. Supplemental digital content is available in the text. Abstract : Background: Previous studies have shown substantial differences in geographic clustering of sexually transmitted infections (STI), such as chlamydia (CT) and gonorrhea (NG), conditional on epidemic phase. Chlamydia and NG have recently shown resurgent epidemiology in the northern hemisphere. This study describes the recent epidemiology of CT and NG in Winnipeg, Canada, combining traditional surveillance tools with place-based analyses, and comparing the ecological niches of CT and NG, in the context of their evolving epidemiology. Methods: Data were collected as part of routine public health surveillance between 2007 and 2016. Secular trends for CT and NG, and CT/NG coinfection were examined. Gini coefficients and population attributable fractions explored the distribution, and concentration of infections over time and space. Results: Rates of CT increased from 394.9/100, 000 population to 476.2/100, 000 population from 2007 to 2016. Gonorrhea rates increased from 78.0/100, 000 population to 143.5/100, 000 population during the same period. Each pathogen had its own ecological niche: CT was widespread geographically and socio-demographically, while NG was clustered in Winnipeg's inner-core. CT/NG co-infections had the narrowest space and age distribution. NG was shown to be undergoing a growth phase, with clear signs of geographic dispersion. The expansion of NG resembled the geographic distribution of CT. Conclusions: We demonstrated that NG was experiencing a growth phase, confirming theoretical predictions of geographic dispersion during a growth phase. During this phase, NG occupied similar geographic spaces as CT. Knowledge of different ecological niches could lead to better targeting of resources for subpopulations vulnerable to STIs.